Characterization of floral traits of BRRI developed component lines of hybrid rice - Hasan, MJ; Kulsum, Umma; Rahman, MH; Akter, A; Hossain, MK (Bangladesh Journal of Plant Breeding and Genetics, 2011)
Bangladesh Journal of Plant Breeding and Genetics, Vol.22(2) December 2009 47-50